A Comparative Study of Azithromycin Versus Doxycycline in the Treatment of Acne Vulgaris - A Amatya; M K Chaudhary; D K Khan; E A Rajouria (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v10i1.6421 NJDVL 2012; 10(1): 33-40